Magical realism in West African fiction : seeing with a third eye - Cooper, Brenda (London ; New York : Routledge, 1998)
This study contextualizes magical realism within current debates and theories of postcoloniality and examines the fiction of three of its West African pioneers: Syl Cheney-Coker of Sierra Leone, Ben Okri of Nigeria and Kojo Laing of Ghana. Brenda Cooper explores the distinct elements of the genre in a West African context, and in relation to: * a range of global expressions of magical realism, from the work of Gabriel Garcia Marquez to that of Salman Rushdie * wider contemporary trends in African writing, with particular attention to how the realism of authors such as Chinua Achebe an.
Seeing with a third eye -- 'Sacred names into profane spaces' : magical realism -- An endless forest of terrible creatures : magical realism in West Africa -- 'Out of the centre of my forehead, an eye opened' : Ben Okri's The famished road -- 'The plantation blood in his veins' : Syl Cheney-Coker and The last harmattan of Alusine Dunbar -- Intermediate magic and the fiction of B. Kojo Laing -- 'Old Gods, new worlds' : some conclusions.
Includes bibliographical references (pages 227-246) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Cheney-Coker, Syl, -- 1945- -- Criticism and interpretation; Laing, B. Kojo -- Criticism and interpretation; Okri, Ben -- Criticism and interpretation; Cheney-Coker, Syl, -- 1945-; Laing, B. Kojo; Okri, Ben; West African fiction (English) -- History and criticism; Postcolonialism -- Africa, West; Postcolonialism in literature; Africa, West -- In literature; Magic realism (Literature); Roman ouest-africain (anglais) -- Histoire et critique; Postcolonialisme -- Afrique occidentale; Postcolonialisme dans la littérature.; Afrique occidentale -- Dans la littérature.; Réalisme magique (Littérature); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Literature; Magic realism (Literature); Postcolonialism; Postcolonialism in literature; West African fiction (English); West Africa; Fictie; Engels; Magisch realisme; West-Afrika.; Magic realism (Literature); Criticism, interpretation, etc